Buffering Effect of Job Resources in the Relationship between Job Demands and Work-to-Private-Life Interference: A Study among Health-Care Workers - Sara Viotti; Daniela Converso (Elsevier, 2016)
Background: The present study aims at investigating whether and how (1) job demands and job resources are associated with work-to-private-life interference (WLI) and (2) job resources moderate the relationship between job demands and WLI. Methods: Data were collected by a self-report questionnaire from three hospitals in Italy. The sample consisted of 889 health-care workers. Results: All job demands (i.e., quantitative demands, disproportionate patient expectations, and verbal aggression) and job resources (i.e., job autonomy, support from superiors and colleagues, fairness, and organizational support), with the exception of skill discretion, were related to WLI. The effects of quantitative demands on WLI were moderated by support from superiors; fairness and organizational support moderate the effects of all job demands considered. Support from colleagues moderated only verbal aggression. Job autonomy did not buffer any job demands. Conclusion: The present study suggests that the work context has a central importance in relation to the experience of WLI among health-care workers. The results indicated that intervention in the work context may help to contain WLI. Such interventions would especially be aimed at improving the social climate within the unit and quality of the organizational process.